A new two-way artificial boundary condition for wave propagation (2017)
We propose a new formulation of a two-way artificial boundary condition for the wave equation in mixed form. We justify appropriately the idea behind the formulation of the two-way artificial boundary condition. To exhibit the capabilities of the two-way artificial boundary condition we perform a set of analytical tests. All tests performed are passed satisfactorily which reassures the applicability of the formulation as a two-way artificial boundary condition. The two-way artificial boundary condition does not require non-linear solvers or iterations on the boundary which makes it computationally efficient. Additionally, it can be easily implemented into existing finite element codes. © 2017, American Institute of Aeronautics and Astronautics Inc, AIAA. All rights reserved.